2021
DOI: 10.1038/s41598-021-88769-5
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of prepulse inhibition is associated with compulsive behavior severity and nucleus accumbens dopamine receptor changes in Sapap3 knockout mice

Abstract: Obsessive compulsive disorder (OCD) is associated with disruption of sensorimotor gating, which may contribute to difficulties inhibiting intrusive thoughts and compulsive rituals. Neural mechanisms underlying these disturbances are unclear; however, striatal dopamine is implicated in regulation of sensorimotor gating and OCD pathophysiology. The goal of this study was to examine the relationships between sensorimotor gating, compulsive behavior, and striatal dopamine receptor levels in Sapap3 knockout mice (K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 54 publications
1
12
1
Order By: Relevance
“…PPI of the acoustic startle response is modulated by CSTC circuit function and impaired in OCD and other neuropsychiatric disorders [ 22 24 ]. To assess PPI, we first tested basal acoustic startle response (SR) to different intensity sound pulses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PPI of the acoustic startle response is modulated by CSTC circuit function and impaired in OCD and other neuropsychiatric disorders [ 22 24 ]. To assess PPI, we first tested basal acoustic startle response (SR) to different intensity sound pulses.…”
Section: Resultsmentioning
confidence: 99%
“…Self-grooming is an innate rodent behavior characterized by a sequential pattern of movements [ 43 ], which serves as a useful proxy for compulsive behavior [ 24 , 44 , 45 ]. Grooming time and frequency are under control by the efferent activity of striatal SPNs.…”
Section: Discussionmentioning
confidence: 99%
“…Grooming is not classically considered to be a coping behavior in response to a stressor; animals will self-groom under low and/or high stress conditions (Kalueff et al, 2016; Smolinsky et al, 2009). However, animal models of obsessive-compulsive disorder (OCD) and Tourette Syndrome (TS) demonstrate high levels of repetitive self-grooming behavior (Manning et al, 2021; Nordstrom and Burton, 2002; Welch et al, 2007), and grooming can be elicited by central infusions of ACTH or DA agonists (Guild and Dunn, 1982; Taylor et al, 2010). The ACTH-induced grooming response was prevented by drugs that block DA receptors, while grooming induced by central ACTH infusion is augmented by the DA agonist apomorphine (Guild and Dunn, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, administration of the α 1 AR antagonist prazosin or the inhibitory α 2 -autoreceptor agonist clonidine reduces tic behavior in the D1CT model of TS, which exhibit neuronal hyperactivity in the PFC that dysregulates the cortico-striato-thalamico-cortical (CSTC) loop (Godar et al, 2016; Nordstrom et al, 2015). The Sapap3−/− model of OCD, which also displays excessive grooming behavior and hyperactivity of the PFC, is associated with abnormalities in DA receptor expression in the CTSC loop (Ahmari et al, 2013; Manning et al, 2019; Manning et al, 2021). Plausibly, persistent excitation of PFC neurons by stress-induced catecholamine release may be a causal mechanism for increased repetitive behavior in patients with compulsive disorders and in animal models featuring excessive grooming as part of their phenotypes (Kasar and Yurteri, 2020; Leckman et al, 1995; McGrath et al, 1999; Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond participating in glutamatergic system, SAPAPs have been implicated in modulating the monoaminergic system. Sapap3 -mutant mice display upregulation of serotonin turnover in cortical and striatal regions and dihydroxyphenylacetic acid/dopamine ratios in the OFC [ 108 ], along with alterations in dopamine receptor density within the NAc [ 109 ], indicating an important role of SAPAP proteins in glutamate–monoamine interplay, which is relevant in psychiatric disorders such as schizophrenia, mood disorders, and OCD [ 110 , 111 ]. A follow-up study revealed an anomalous excessive form of synaptic plasticity (i.e., endocannabinoid-mediated LTD) expressed at striatal excitatory synapses, requiring mGluR5 signaling in Sapap3 -mutant mice [ 99 ].…”
Section: Roles Of Sapaps In Synaptic Structure and Functionmentioning
confidence: 99%